Analisis Fitokimia Dan Toksisitas Dari Ekstrak Daun Tumbuhan Mempening (Lithocarpus bancanus (Scheff.) Rehd) Menggunakan Metode BSLT (Brine Shrimp Lethality Test) - Retno Puji Lestari; Rudi Hendra Sy; Hilwan Yuda Teruna (JURNAL FARMASI DAN MAKANAN, 2019)
Mempening (Lithocarpus bancanus (Scheff.) Rehd) is a species belongs to the family Fagaceae which is found growing around the Talang Mamak tribal region in Kelayang District, Indragiri Hulu Regency, Riau Province. The purpose of this study was to determine the toxicity of leaf extract of L. bancanus (Scheff.) Rehd against Artemia salina Leach larvae using the Brine Shrimp Lethality Test (BSLT) method and its phytochemical analysis. The results of the toxicity was determined against n-hexane, dichloromethane, ethyl acetate, methanol, and ethanol extract and they showed LC50 values ​​of 3.15 ppm; 41163.26 ppm; 5817.09 ppm; 817, 27 ppm; 9019.70 ppm. Phytochemical analysis of the leaves of L. bancanus (Scheff.) Rehd plant showed a class of flavonoids, terpenoids, phenolics and saponins.